Reanalysis of the β - ν[bar]e angular correlation measurement from the aSPECT experiment with new constraints on Fierz interference - Beck, Marcus; Heil, W.; Schmidt, Ch.; Baeßler, S.; Glück, F.; Konrad, G.; Schmidt, Ulrich (Physical review letters, 2024)
On the basis of revisions of some of the systematic errors, we reanalyzed the electron-antineutrino angular correlation (𝑎 coefficient) in free neutron decay inferred from the recoil energy spectrum of the protons which are detected in 4⁢𝜋 by the aSPECT spectrometer. With 𝑎=−0.104 02⁢(82) the new value differs only marginally from the one published in 2020. The experiment also has sensitivity to 𝑏, the Fierz interference term. From a correlated (𝑏,𝑎) fit to the proton recoil spectrum, we derive a limit of 𝑏 =−0.0098⁢(193) which translates into a somewhat improved 90% confidence interval region of −0.041 ≤𝑏 ≤0.022 on this hypothetical term. Tighter constraints on 𝑏 can be set from a combined [shown as superscript (𝑐)] analysis of the PERKEO III (𝛽 asymmetry) and aSPECT measurement which suggests a finite value of 𝑏 with 𝑏(𝑐)=−0.0181±0.0065 deviating by 2.82⁢𝜎 from the standard model.